INFLUENCE OF LENTIL (LENS ESCULENTA M.) GENOTYPES ON ARBUSCULAR MYCORRHIZAL COLONIZATION INTENSITY AND POPULATION DENSITY - S. NGOMLE,; J. SAHA,; R. NATH,; B. N. PANJA, (The Bioscan, 2014)
Forty lentil genotypes were evaluated under field condition for two consecutive seasons to see the range of AM fungal colonization and spore population density and to group into high medium and low categoties. Results showed that spore population density and root colonization intensity of these genotypes were found to vary from 22 - 81 (per 30 g dry soil) and 55.1 - 96.2% respectively. Spore number was found highest with the genotype L338 (81 spore/30 gm of soil) followed by L- 245 (77 spore/30 gm of soil) and others whereas it was observed lowest with L-317 (22 spore/30 gm of soil) . Root colonization intensity was found highest with Hull - 57 (96.2 %), remained at par with L- 311 (94.9 %), L- 330 (94.1 %) followed by L- 225 (91.4 %) and others whereas it was observed lowest with L - 223 (55.1%). Based on population density, genotypes placed under low (22 - 35), medium (36 - 65) and high (66 - 81) [per 30 g dry soil]. Based on root colonization intensity, genotypes placed under low (0 - 30%), medium (31 - 60%) and high (61 - 100%) categories. Lentil genotypes grown under field condition cause differential stimulation of AMF spore numbers, exhibit variations in their level of colonization and be arbitrarily grouped into low, medium and high categories .So, for increasing lentil produvtivity suitable genotypes can be picked up from the cafeteria of lentil genotypes having high value of spore population density and root colonization intensity.